Statistical Measurements of Technology Adoption Among Unstructured Retailers - Joydeep Mookerjee, Subir Chattopadhyay (Mathematical Statistician and Engineering Applications, 2022)
Innovations have been made in retail due to the rapid development of digital and automated technologies. Retail technology is leveraging advances and digital technologies in the retail and e-commerce industries to improve the shopping experience. Therefore, we may conclude that the integration of retail technology into a firm has a direct impact on the consumer experience. Now, both brick-and-mortar and online retailers engage in various facets of this technology to match customers’ expectations for the shopping experience. The retail industry in India has seen several revolutions and expanded significantly during the past decade. As a result of the epidemic, the retail industry is undergoing significant change. India’s retail sector’s rapid use of technology contributes to the industry’s expansion. As a result, we may conclude that India has the most promising future in retail technology. From 2019 to 2030, Kearney Research anticipates a 9% increase in India’s retail industry. By 2030, the retail sector’s market will reach 1.8 trillion. This paper illustrates the measurement of technology adoption distribution among retailers in Kolkata. For this empirical study, 110 retailers were randomly chosen from the suburban markets of Kolkata.